Angle Robust Reflection/Transmission Plasmonic Filters Using Ultrathin Metal Patch Array. Issue 12 (16th September 2016) - Yang, Chenying; Shen, Weidong; Zhou, Jing; Fang, Xu; Zhao, Ding; Zhang, Xing; Ji, Chengang; Fang, Bo; Zhang, Yueguang; Liu, Xu; Guo, L. Jay
Abstract : Angle robust reflection/transmission plasmonic filters using ultrathin metal patch array are proposed to achieve angle insensitive color filtering for a broad range of incidence angles up to 60°. This property is attributed to the localized surface plasmonic resonance of each metal patch. Further, an array with as few as two periods is sufficient to demonstrate the color filtering effect.